Variations of Index (2D) Finger Length among Adult Bangladeshies - Hasan, Karim Rezwan; Ara, Shamim; Begum, Mahamuda (Bangladesh Journal of Anatomy, 2015)
Context: In human hand, the lengths of all digits are not the same. By virtue of evolutionary changes digital lengths vary from person to person according to age, sex, races, occupation or even environmental influences. It has been found that the digital lengths are not even same in both hands of an individual. In this study, this variation of the index finger (2D) length has been analyzed and compared among the adult population of Bangladesh. Materials & Methods: A cross sectional analytical study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from July 2012 to June 2013. The study was performed on 200 MBBS students (18 years of age) of Dhaka Medical College, Dhaka. Among them 100 were male and 100 were female. With the help of digital vernier caliper measurements of digital lengths were recorded. Paired and unpaired students t tests were done for statistical analysis of the results. Results: The mean length value of right index finger (R2D) and left index finger (L2D) was greater in male than female (P<0.001). Significant difference between the length of right index finger (R2D) and left index finger (L2D) was observed in male (P<0.05) where left index finger length (L2D) was slightly higher than right index finger length (R2D) but in female the difference was not significant (P> 0.05). Conclusion: Digital lengths especially index (2D) and ring (4D) finger lengths are often use to determine sexual dimorphism. Also, study over the variations of digital lengths have great medicolegal importance to determine age, sex and race of an individual. Bangladesh J. Anat. 2015; 13(1) : 27-31